SAT0047 Local Cryotherapy Down-Regulates Local and Systemic IL-6 and IL-17 Pathways in Adjuvant-Induced Arthritis. (15th July 2016) - Guillot, X.; Martin, H.; Maguin-Gaté, K.; Py, S.; Demougeot, C.; Wendling, D.; Tordi, N.
Abstract : Background: Cryotherapy is widely and empirically used in an adjuvant and symptomatic setting in inflammatory rheumatic diseases, with a low level of evidence [1]. Objectives: The aim of this work was to evaluate local and systemic anti-inflammatory effects of local cryotherapy (LC) in adjuvant-induced arthritis (AIA), comparing 2 techniques (ice and cold gas spray). We considered clinical (arthritic score and ankle diameter) and biological effects on IL-6, IL-17A, IL-1β, TNF-α local and systemic levels. Methods: Arthritis was induced by a single Mycobacterium butyricum injection in male Lewis rat tails (day 0). At the onset of arthritis (day 11), rats were treated either by 30 minute-ice applications on hind paws (in cages lined with ice pops – n=10) or by 2 minute-cold gas pulverizations on both hind paws (n=9) twice a day for 14 consecutive days. Ten non-treated AIA rats were used as controls. At day 24 (the day after the last cold application), hind paws were grinded in order to measure cytokine gene expression levels by Q-RT-PCR. Plasmatic levels of the same cytokines were also measured in plasma by cytometry (Multiplex Magpix® ebioscience). IL-6 plasma levels were measured by ELISA (rat IL6 platinum ELISA, BMS625®, ebioscience). Results: Ice application significantly reduced the mean arthritic score and ankle diameter from day 6 to day 14 (p<0.001) and globally throughout the 14 day treatment period (2-way ANOVA: p<0.001) compared to non-treated AIA controls. Cold gas first aggravated arthritis at days 11–12 (p<0.01) then improved clinical inflammation at days 21–24 (p<0.001). Skin temperature after LC didn't differ between treatment groups. Both techniques significantly reduced IL-6, IL-1β, IL-17A gene expression levels in hind paws at day 24 compared to non-treated AIA (by 60%, 87% and 50% respectively, p<0.001, p<0.001 and p<0.05). Cytokine gene expression levels correlated positively with hind paw arthritic score and ankle diameter. Conversely, LC had no effect on TNF-α gene expression in hind paws. LC also significantly reduced IL-17A plasmatic protein levels at day 24 (Ice: 47±3pg/ml versus 132±15pg/ml; n=9; p<00001 – cold gas: 89±12pg/ml versus 132±15pg/ml; p<0.02) and IL-17A plasmatic levels correlated positively with arthritic score, ankle diameter and negatively with weight gain. Ice also reduced IL-6 plasmatic levels (118±20pg/ml versus 197±60pg/ml; p<0.05). LC had no effect on TNF-α nor IL-1β plasmatic levels. Conclusions: These results demonstrate in vivo previously unknown therapeutic and anti-inflammatory effects of 14 day-LC in AIA. We observed both local (at the gene level in treated hind paws) and systemic (at the protein level in plasma) down-regulation of key cytokine pathways critically involved in the pathogenesis and severity of inflammatory rheumatic diseases. LC local and systemic anti-inflammatory effects were mainly IL-6/IL-17A-driven and TNF-α-independent in this model. References: Guillot X, et al. Cryotherapy in inflammatory rheumatic diseases: a systematic review. Expert Rev Clin Immunol. 2014;10(2):281–94. Disclosure of Interest: None declared